Comparison of Microbiological Examination by Test Tube and Congo Red Agar Methods to Detect Biofilm Production on Clinical Isolates - Furtuna, Dewi Klarita; Debora, Kartuti; Warsito, Eddy Bagus (Folia Medica Indonesiana, 2018)
Biofilm on medical devices can cause significant diseases and deaths and give a large effecton disease transmission among patients and health providers and potentially increasethe cost of patient treatment. By knowing the presence of biofilm on a patient, one can differentiate the treatment management for that particular patient from the patients without biofilm on their medical device. The purpose of this study was to obtain diagnostic method to detect biofilm formation on isolates from the medical devices by simple method that is easy to do and can be applied in resource-limited microbiology laboratory. 36 specimens obtained from IV Line, CVC, urinary catheter and ETT were grown on Muller Hinton agar and continued with 3 methods, i.e., Test Tube method, Congo Red Agar method and Microtiter Plate Assay method. Results of this study showed Test Tube (nephelometer), Test Tube (visual) and Congo Red Agar in order to have the same sensitivity of 100% but has higher specificity compared to Test Tube method (visual) and Congo Red Agar method in detecting biofilm production on isolates from medical devices that had been plugged into patients body. The biofilm formation inside devices depends on factors, i.e., host, device and the microorganism itself.